A cross-sectional study of the clinical profile of children admitted with yellow phosphorous poisoning in a tertiary care hospital - Selvaraju K; Vijay Anand M; Kanimozhi P; Anurekha V; Sanjay PM; Kumaravel KS (Asian Journal of Medical Sciences, 2023)
Background: Yellow phosphorous (YP) is a protoplasmic poison that is mainly used as a rodenticide. Aims and Objectives: The aim of the study is to describe the clinical profile of YP poisoning in children in a tertiary care hospital. Materials and Methods: This is a cross-sectional study done in a tertiary care hospital in Tamil Nadu. A convenience sample of all the cases admitted during the year 2022 was done. Demographic and clinical data were collected and analyzed. Results: The male: female ratio was 1.16:1 (n=13). The mean age of the children was 4.0769±1.373 years. About 84.61% of the children reported to the hospital within 6 h. On admission, fever (30.76%), vomiting (30.76%), abdominal pain (30.76%), bleeding (15.38%), and altered sensorium (15.38%) were the common symptoms. All the children ingested YP accidentally. Leukocytosis was observed in about 30.76%. The mean peak serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were 516.9231±685.976 IU/L and 161.9231±215.107 IU/L, respectively. There were no alterations in the Electrocardiographic tracings, levels of serum electrolytes, blood glucose, and serum creatinine in children with YP poisoning. Significant differences were observed between children who survived and children who died in the levels of mean peak AST, mean peak ALT, INR, and in the presence of encephalopathy and bleeding manifestations. Conclusion: YP is an uncommon but lethal poison in children. Creating awareness among parents about the dangers of YP and nationwide prohibition of the sale of YP will be an important step in eliminating deaths in children who are accidental victims.